Impact of Livelihood Assets on Farmland-Transferred Households’ Willingness to Urbanism and Policies Implications for Farmland Transfer: Evidence from Zhejiang, China - Heyuan You; Xiaowei Hu; Chenmeng Bie; Deshao Zhou (Discrete Dynamics in Nature and Society)
The rural households who transfer their farmland are more likely to migrate into urban cities in China. Understanding their willingness to urbanism can provide references for promoting China’s new-type urbanization. Using structural equation modeling (SEM), this study analyzes the effect of livelihood assets on farmland-transferred households’ willingness to urbanism in Zhejiang province in China. The results show that there is no relationship between natural capital (NC) and willingness to urbanism (UI). Statistically significant negative relationships are identified between human capital (HC), financial capital (FC), and social capital (SC), respectively, and UI. Physical capital (PC) has a statistically significant and positive relationship with UI. The findings demonstrate that the farmland transfer characteristics have different effects on farmland-transferred households’ livelihood assets. Benefit of farmland transfer (BFT) has a statistically significant positive influence on HC, FC, and SC. Meanwhile, PC, FC, and SC are positively affected by openness in farmland transfer (OFT). Based on these profiles, Chinese local governments should design more livelihood-oriented policies to help farmland-transferred households raise willingness to urbanism in the process of operation right transfer under Three Rights Separation Policy for farmland.